PEMODELAN SISTEM UNTUK APLIKASI PENGELOLAAN PEMBERIAN DANA BANTUAN WARGA MISKIN DI JAKARTA - Ita Novita; M. Anif (Bit (Fakultas Teknologi Informasi Universitas Budi Luhur), 2012)
There is a problem with the unavailability of information on grant management for supporting poor people in Jakarta. This information on grant should be in terms of information on location area, where the poor people will receive assistance, how much they need and the form of grant the poor people expected. Therefore, application of this information should be developed in order to support all application of the grant. The first important step is to develop a good modeling system which produces integrated application in order to avoid error in applying the system. The modeling system is using object oriented approach by using Unified Modeling Language (UML). This technique modeling system will be realized in the form of case study which is a system modeling for application of grant management for poor people in Jakarta. The result of this modeling system is only to get the database which further can be used for developing application software. The software used for this system modeling is Rational Rose Enterprise 2000.Keywords : Poor People, Systems Modeling, Giving Fund, Unified Modeling Language (UML)